Identification of novel sources of resistance to white rust (Puccinia horiana) inChrysanthemum (Chrysanthemum morifolium) - Bennurmath, P; Kumar, R; Sriram, S; Venugopalan, R; Gurung, A (Journal of Horticultural Sciences, 2025)
Chrysanthemum is a premier commercial floriculture crop valued for its versatility as a loose flower for garlands, a cut flower for arrangements, and an ornamental pot or bedding plant. However, white rust, caused by Puccinia horiana Henn., remains a major pathological constraint resulting in significant economic losses. This study evaluated the resistance of 175 chrysanthemum genotypes under natural field conditions, with a subset of 20 genotypes further validated via in vitro detached leaf assays. Results indicated that 18 genotypes were highly susceptible, recording the highest per cent disease index (PDI > 61%). Conversely, 27 genotypes were categorized as resistant (PDI 11–20%), while, the remaining genotypes exhibited no symptoms (PDI 1–10%) and were classified as highly resistant. Notably, genotypes such as Mayur, NBRI Little Kusum, and Arka Yellow Gold demonstrated consistent high resistance, while, genotype Marigold, Sunil, and Punjab Gold were susceptible across both screening environments. These identified resistant genotypes serve as valuable genetic resource for commercial cultivation and future breeding programs aimed at disease resistance.
Keywords: Chrysanthemum; per cent disease index; resistance; screening; white rust